TELEMEDICINE AND DIGITAL HEALTH PLATFORMS: EVIDENCE FROM LOW- AND MIDDLE-INCOME COUNTRIES AND IMPLICATIONS FOR CENTRAL ASIA (Global Conference on Medical and Health Sciences, 2026)
This article presents a systematic literature review of telemedicine and digital health platform evidence from low- and middle-income countries (LMICs), examining effectiveness, implementation determinants, and economic implications relevant to Central Asian healthcare systems. Publications from 2012 to 2024 indexed in PubMed, Scopus, WHO Global Health Observatory, and Cochrane Library were analysed. The review covers synchronous and asynchronous telemedicine modalities, mobile health (mHealth) applications, teleconsultation platforms, remote patient monitoring, and digital health ecosystem development. The analysis demonstrates that telemedicine interventions in LMICs produce clinically meaningful improvements in healthcare access — reducing travel distances for specialist consultation by 60–80% in documented programmes — alongside modest but consistent improvements in chronic disease management outcomes including HbA1c reduction, blood pressure control, and medication adherence. Implementation is critically dependent on mobile internet infrastructure, digital literacy, and healthcare worker training. The review identifies telemedicine's substantial potential for addressing specialist access inequalities in Uzbekistan and outlines a framework for evidence-based digital health platform development.
Keywords: telemedicine, digital health, mHealth, remote consultation, low- and middle-income countries, healthcare access, Uzbekistan, literature review.